Practicum Design for Making Edible Film from Starch Based on STEM to Improve Student Creativity in Learning Polymer Topics - Tri Suharti Jupita; Mulyati Arifin; Hayat Solihin (Universitas Riau, 2021)
One of the 21st century skills that students need is creativity. Creativity in Indonesia is still lacking based on several previous studies. Therefore, learning innovations are needed that can increase student creativity, namely through STEM-based practicum learning. This STEM-based practicum learning integrates aspects of Science, Technology, Engineering and Mathematics in practicum learning. This research aims to produce a STEM-based practicum design for making edible films from starch poured in worksheets. The research method used the DBR (Design Based Research) method. The steps of this research are: 1) Design of practicum design, 2) Optimization results of practicum design for making edible film from starch, 3) Analysis of the relationship between the curriculum on the topic of polymer with STEM and creativity aspects, 4) Analysis of the existence of practicum procedures for making edible films in high school chemistry books class XII, 5) Expert validation. The data collection technique is done by studying the literature, optimizing the experimental results of the practicum design and the results of validation. Data analysis was performed by calculating the percentage of each aspect and interpreting it in the validation criteria table and the result was 91% with very valid categories.